Effects of obesogenic diet and 17β-estradiol in female mice with APOE 3/3, 3/4, and 4/4 genotypes - Christensen, Amy; McGill, Cassandra J.; Qian, Wenjie; Pike, Christian J. (Frontiers in Aging Neuroscience, 2024)
The main genetic risk factor for Alzheimer's disease (AD) is the apolipoprotein E ε4 allele (APOE4). AD risk associated with APOE4 disproportionately affects women. Further, human and rodent studies indicate that the cognitive deficits associated with APOE4 are greater in females.One modifiable AD risk factor is obesity during middle-age. Given that about two-thirds of US adults are overweight, it is important to understand how obesity affects AD risk, how it interacts with APOE4, and the extent to which its detrimental effects can be mitigated with therapeutics.One intervention studied for women is estrogen-based hormone therapy, which can exert numerous health benefits when administered in early middle-age. No experimental studies have examined the interactions among APOE4, obesity, and hormone therapy in aging females. To begin to explore these issues, we considered how obesity outcomes are affected by treatment with estradiol at the onset of middle-age in female mice with human APOE3 and APOE4. Further, to explore how gene dosage affects outcomes, we compared mice homozygous for APOE3 (3/3) and homozygous (4/4) or hemizygous (3/4) for APOE4. Mice were examined over a four-month period that spans the transition into reproductive senescence, a normal age-related change that models many aspects of human perimenopause. Beginning at 5 months of age, mice were maintained on a control diet (10% fat) or high-fat diet (HFD; 60% fat). After 8 weeks, by which time obesity was present in all HFD groups, mice were implanted with an estradiol or vehicle capsule that was maintained for the final 8 weeks. Animals were assessed on a range of metabolic and neural measures. Overall, APOE4 was associated with poorer metabolic function and cognitive performance. However, obesogenic diet induced relatively greater impairments in metabolic function and cognitive performance in APOE3/3 mice. Estradiol treatment improved metabolic and cognitive outcomes across all HFD groups, with APOE4/4 generally exhibiting the greatest benefit. APOE3/4 mice were intermediate to the homozygous genotypes on many measures but also exhibited unique profiles. Together, these findings highlight the importance of of estradiol.